Sistem Akuntabilitas Pendanaan Partai Politik - Faturrahman, Muhammad (Jurnal Administrasi Politik dan Sosial, 2024)
The accountability system for political party funding is a very crucial indicator in measuring the strength of integrity and transparency of a political party. Political parties play a vital role in the implementation of the political system in Indonesia and become a buffer between the needs (aspirations) of the people and the government. It cannot be argued that political parties in carrying out their duties and functions need financial assistance or funding to maintain the existence of the party and also to make it easier for political parties to accelerate activities oriented towards public services. The source of funding to political parties has been strictly guaranteed by the state through various laws and regulations, so that the logical consequence of each rule is the existence of an element of accountability, in this case after a political party has obtained funding rights from the state or the private sector, then the political party is obliged to enforce an accountability system in the form of an integrity and transparent funding report as a form of openness to the public. On that basis, this study aims to analyze the funding arrangements given to political parties by examining the accountability system for funding guided by the established regulations and identifying challenges related to the accountability system of political party funding and providing recommendations on the challenges faced. The method is in the form of qualitative studies using descriptive analysis, which involves regulatory analysis, in-depth interviews, data and documents that have relevance to the research topic.